Ferrous sulfide composite material for removing nitrate in water body and preparation method of ferrous sulfide composite material

By combining the modification of sodium alginate and zero-valent iron on ferrous sulfide, a sodium alginate stable zero-valent iron-modified ferrous sulfide composite material with high stability and strong reactiveness was prepared, which solved the problem of low nitrate removal efficiency in water bodies and achieved the effect of efficiently removing nitrates in water bodies.

CN119591225AInactive Publication Date: 2025-03-11ANHUI UNIVERSITY OF TECHNOLOGY
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202411826340.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art has problems of poor stability and low reaction activity in removing water nitrates, especially ferrous sulfide is prone to agglomeration and oxidation, which affects its removal efficiency.

Method used

The crosslinked products of sodium alginate and calcium chloride are used as the framework, and ferrous sulfide and zero-valent iron are embedded in it. Sonication and stirring are used to prepare sodium alginate stable zero-valent iron modified ferrous sulfide composite materials.

Benefits of technology

The reactive activity and stability of the composite material are improved, the surface area and pore structure are significantly increased, and the oxidation resistance is enhanced, and the efficiency of water nitrate removal is achieved. The nitrate nitrogen removal rate can reach up to 86%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591225A_ABST
    Figure CN119591225A_ABST
Patent Text Reader

Abstract

The invention provides a ferrous sulfide composite material for removing nitrate in a water body and a preparation method of the ferrous sulfide composite material, and belongs to the technical field of environment functional composite materials. The composite material is prepared by crosslinking sodium alginate and calcium chloride to form a skeleton and embedding ferrous sulfide and zero-valent iron in the skeleton, the preparation method specifically comprises the following steps: adding ferrous sulfide, zero-valent iron and sodium alginate into deionized water, stirring on a magnetic stirrer, dropwise adding the prepared solution into a calcium chloride solution by using an injector after uniformly stirring, and freeze-drying to obtain the sodium alginate stabilized zero-valent iron modified ferrous sulfide composite material. The raw materials are low in cost, the preparation method is simple, the composite material is biodegradable, green and free of secondary pollution, the defects that ferrous sulfide is prone to agglomeration, low in reaction activity and poor in stability are overcome, meanwhile, a more stable removal effect on nitrate in water is achieved, and the water quality is improved. The ferrous sulfide composite material has a good market application prospect for treating nitrate pollution of surface water and underground water.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of environmental functional composite materials, and particularly relates to a sodium alginate-stabilized zero-valent iron-modified ferrous sulfide composite material for removing nitrate from water bodies and a preparation method thereof. Background Art

[0002] Nitrates have been identified as one of the most prevalent pollutants in surface waters worldwide. - Elevated -N levels not only cause eutrophication of water bodies, but also pose a threat to aquatic life and human health. However, the accumulation of nitrogen compounds in low-pollution water sources (such as sewage treatment plant effluent or non-point source pollution) is considered to be one of the causes of eutrophication and ecotoxicity in water bodies. The lack of organic carbon sources in sewage treatment plant effluent leads to heterotrophic denitrification to remove NO3 - -N efficiency is low. Due to the advantages of autotrophic denitrification technology such as low energy consumption, low sludge production, and no carbon source limitation, strengthening NO3 - Autotrophic denitrification of -N is the key to controlling nitrogen emissions from water bodies with low carbon-nitrogen ratios. Developing a low-cost, environmentally friendly material with high nitrate removal performance is of great practical significance.

[0003] The characteristic of autotrophic denitrification is the use of inorganic materials (such as H2, Fe 2+ and S 2- ) acts as an electron and energy donor to enhance the denitrification process to remove nitrogen. 0 ,S - ,S 2- ) electron donors have excellent electron donor capacity and a wide range of sources and have been explored for autotrophic denitrification. FeS is a cheap and widely available inorganic compound that is currently widely used in environmental remediation and pollution management. It can not only provide S 2- ions, and also contains Fe 2+ , can act as an electron donor to participate in NO3 - -N reduction process. At the same time, iron has excellent adsorption capacity and low biological toxicity, so FeS can promote the enrichment of denitrifying bacteria on the FeS surface, thereby improving the efficiency of autotrophic denitrification. Therefore, using FeS to remove nitrate from water bodies has certain theoretical feasibility.

[0004] However, exposed FeS is prone to aggregation and oxidation, reducing its surface area and activity, thereby affecting its reduction efficiency. Therefore, it is necessary to modify it to improve its stability. Encapsulating FeS with a stabilizer is an effective way to solve the above problems. Sodium alginate (SA), as a biodegradable and biocompatible polysaccharide, has good biodegradability, compatibility, adhesion and stability, and is widely used to immobilize various materials. Therefore, the application of SA can effectively improve the dispersibility and antioxidant properties of FeS and enhance its adsorption capacity. In recent years, zero-valent iron (Fe 0 ) is widely used in sewage remediation as an environmentally friendly and low-cost material. 0 The reducibility is strong, and it has a good removal effect on pollutants that can directly accept electrons. In short, the combined modification of FeS with sodium alginate and zero-valent iron is expected to develop a composite functional material with good removal performance and high stability, which is of great significance for the repair of nitrate pollution in water bodies.

[0005] In the prior art, some results have been achieved in the preparation methods of related modified composite materials. For example, Chinese patent application number: 201610022704.8, published on January 14, 2016, disclosed a patent document entitled "A preparation method and application of a zero-valent iron biochar-based repair material". This patent uses a secondary calcination method to load nano zero-valent iron on biochar as a carrier to prepare a nitrate removal composite material with adsorption and reduction capabilities. However, the preparation steps of this material are complicated, which is not conducive to industrial application. Chinese patent application number: 202410968814.8, published on August 23, 2024, disclosed a patent document entitled "A modified biomass charcoal-sodium alginate gel and its preparation method and application". The patent is to carbonize and activate the algae in sequence, and then mix it with water and DTPA-Zn to obtain modified biochar, which is further cross-linked with sodium alginate and calcium chloride; Chinese patent application number: 202311792782.2, published on December 25, 2023, disclosed a patent document entitled "A preparation method and application of sodium alginate-loaded micron sulfur-modified iron hydrogel". The hydrogel in this patent is a skeleton formed by cross-linking sodium alginate and calcium chloride, and then sulfur-modified micron-sized iron hydrogels are cross-linked to form a skeleton. Zero-valent iron is embedded in it; the above two adsorption materials are both encapsulated and modified using sodium alginate, but the core materials are different, and the pollutants removed are also different, resulting in different removal processes and mechanisms; Chinese patent application number: 202311709502.7, application publication date December 13, 2023, the disclosed patent document is named "Spherical hydrotalcite-sodium alginate hydrogel adsorbent and preparation method, application". The invention uses six metal salts as raw materials for the preparation of LDHs, triethanolamine as an alkali source, and a hydrothermal method to prepare LDHs powder with high adsorption performance, and then the LDHs powder is compounded with sodium alginate to obtain solid particle hydrogel balls; however, six metal salts are used in the preparation process, and the preparation process is relatively complicated. Others such as, Chinese patent application number: 202311625158.3, published on January 12, 2024, disclosed a patent document entitled "Application of montmorillonite-loaded sulfide nano zero-valent iron in pollutant removal"; Chinese patent application number: 202010580852, published on August 24, 2021, disclosed a patent document entitled "A sulfide nano zero-valent iron-acid-activated montmorillonite composite material and its preparation method and application"; Chinese patent application number: 202010073989.4, published on January 22, 2020, disclosed a patent document entitled "A preparation method and application of biochar that simultaneously immobilizes ferrous sulfide and zero-valent iron"; the above research results are mostly used to treat volatile organic matter or cationic metal ions in water, and are not suitable for the removal of nitrates in the form of anions in water. Summary of the invention

[0006] In view of the deficiencies of the existing technology in removing nitrate from water and the problems that ferrous sulfide is easy to agglomerate, easy to oxidize, and has poor stability, the technical problem to be solved by the present invention is to provide a ferrous sulfide composite material for removing nitrate from water, so as to improve the reaction activity and stability of the composite material and at the same time have a stable removal effect on nitrate from water.

[0007] To solve the above problems, the present invention adopts the following technical solutions.

[0008] The present invention provides a ferrous sulfide composite material for removing nitrate from water. The composite material uses a cross-linked product of sodium alginate and calcium chloride as a skeleton, and ferrous sulfide and zero-valent iron are embedded in the skeleton. The specific preparation method of the composite material comprises the following steps:

[0009] (1) Weighing sodium alginate, ferrous sulfide and zero-valent iron powder and adding them into a headspace bottle filled with deionized water, ultrasonically treating them in an ultrasonic cleaner, placing the headspace bottle on a magnetic stirrer for stirring, and obtaining a sol;

[0010] The mass ratio of the sodium alginate to ferrous sulfide is 1-5:5; the mass ratio of the ferrous sulfide to zero-valent iron is 1:1.

[0011] (2) using a disposable syringe to extrude the sol prepared in step (1) into a calcium chloride solution to obtain sodium alginate hydrogel microspheres; during the entire gelation process, the calcium chloride solution is stirred to accelerate mass transfer and prevent the gel microspheres from sticking together.

[0012] (3) pouring the hydrogel microspheres obtained in step (2) into deionized water and filtering through gauze; then repeatedly rinsing with deionized water until the impurities and excess calcium ions and chloride ions on the surface of the composite gel microspheres are washed away, and then freeze-drying the prepared sodium alginate hydrogel microspheres to obtain a sodium alginate-stabilized zero-valent iron modified ferrous sulfide composite material.

[0013] Furthermore, in step (1), the mass ratio of sodium alginate to ferrous sulfide is 3:5.

[0014] Furthermore, in step (1), the deionized water is purified with N2 for 20 minutes.

[0015] Furthermore, in step (2), the mass fraction of the calcium chloride solution is 2%.

[0016] Furthermore, in step (3), the freeze-drying temperature is -40°C; and the freezing time is more than 24 hours.

[0017] The sodium alginate-stabilized zero-valent iron-modified ferrous sulfide composite material prepared by the invention can be applied to the removal of nitrates in surface water and groundwater.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] (1) The modified ferrous sulfide composite material of the present invention has a rich pore structure, a significantly increased surface area, an increased effective reaction area, improved oxidation resistance and stability, and enables the ferrous sulfide to have more surface reaction sites, thereby having a higher removal rate for nitrate (the nitrate nitrogen removal rate can reach up to 86%).

[0020] (2) In the preparation process of the present invention, ferrous sulfide is jointly modified by sodium alginate and zero-valent iron, which has both coupling and dispersion functions and plays a synergistic role. The obtained composite material improves the problems of ferrous sulfide being easy to agglomerate, easy to oxidize, low reaction activity, and poor stability. At the same time, it expands the application scope of ferrous sulfide materials and is convenient for practical application.

[0021] (3) The raw materials for preparing the modified ferrous sulfide composite material of the present invention are widely available and inexpensive. Sodium alginate is biodegradable and belongs to renewable resources and environmentally friendly materials. Ferrous sulfide and zero-valent iron have excellent adsorption capacity and low biological toxicity.

[0022] (4) The sodium alginate-stabilized zero-valent iron-modified ferrous sulfide composite material of the present invention has good market application prospects for treating nitrate pollution in surface water and groundwater. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The sodium alginate-stabilized zero-valent iron-modified ferrous sulfide composite material obtained in Example 1 of the present invention is coupled with a sludge system to react with NO3 - -N removal effect diagram.

[0024] Figure 2 The figures are scanning electron microscope images of the sodium alginate-stabilized zero-valent iron-modified ferrous sulfide composite material obtained in Example 1 of the present invention before and after the reaction; wherein: (A) is the material before the experimental reaction, (B) is the material after the reaction without inoculation of anaerobic sludge, and (C) is the material after the reaction with inoculation of anaerobic sludge.

[0025] Figure 3 This is the XRD diagram of the sodium alginate-stabilized zero-valent iron-modified ferrous sulfide composite material obtained in Example 1 of the present invention before and after inoculation with anaerobic sludge reaction.

[0026] Figure 4The XPS graph of the sodium alginate-stabilized zero-valent iron-modified ferrous sulfide composite material obtained by the implementation of the present invention after reaction; wherein: (A) is the full spectrum of the material after reaction without inoculation of anaerobic sludge, (A1) is the iron element spectrum of the material after reaction without inoculation of anaerobic sludge, (A2) is the sulfur element spectrum of the material after reaction without inoculation of anaerobic sludge, (B) is the full spectrum of the material after reaction with inoculation of anaerobic sludge, (B1) is the iron element spectrum of the material after reaction with inoculation of anaerobic sludge, and (B2) is the sulfur element spectrum of the material after reaction with inoculation of anaerobic sludge. DETAILED DESCRIPTION

[0027] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments, but is not intended to be a specific limitation of the present invention.

[0028] Example 1

[0029] This embodiment provides a method for preparing a composite material of sodium alginate-stabilized zero-valent iron modified ferrous sulfide (the mass ratio of ferrous sulfide to zero-valent iron is 1:1, and the mass ratio of sodium alginate to ferrous sulfide is 3:5), the method comprising the following steps:

[0030] (1) Preparation of mixed solution of ferrous sulfide and zero-valent iron: The deionized water used in the experiment was purified with N2 for 20 min. A 100-mL beaker was filled with 50 mL of deionized water. 2.5 g of ferrous sulfide powder and 2.5 g of iron powder were weighed and added to the beaker. The mixed solution of ferrous sulfide and zero-valent iron was set aside.

[0031] (2) Preparation of a mixed sol of sodium alginate, ferrous sulfide and zero-valent iron: Place a beaker on a magnetic stirrer and stir at a speed of 100 rpm. Weigh 1.5 g of sodium alginate and add it to the beaker and stir for 15 minutes to ensure that a uniform and oxygen-free mixed sol of sodium alginate, ferrous sulfide and zero-valent iron is obtained.

[0032] (3) Preparation of sodium alginate-stabilized zero-valent iron-modified ferrous sulfide composites: The above solution was squeezed into 100 mL of calcium chloride solution (2%, w / v) using a 10 mL disposable syringe. During the entire gelation process, the calcium chloride solution was stirred to accelerate mass transfer and prevent the gel microspheres from sticking together.

[0033] After 5 minutes, the mixture was poured into 100 mL of deionized water, gently stirred for 5 seconds, and then filtered through a piece of gauze. The mixture was then repeatedly rinsed with deionized water until the impurities and excess calcium ions and chloride ions on the surface of the composite gel spheres were washed away, and then the prepared sodium alginate hydrogel microspheres were placed in a freeze dryer at -40°C to obtain a sodium alginate-stabilized zero-valent iron-modified ferrous sulfide composite material.

[0034] Example 2

[0035] This embodiment provides a method for preparing a composite material of sodium alginate-stabilized zero-valent iron modified ferrous sulfide (the mass ratio of ferrous sulfide to zero-valent iron is 1:1, and the mass ratio of sodium alginate to ferrous sulfide is 1:5), the method comprising the following steps:

[0036] (1) The mixed solution of ferrous sulfide and zero-valent iron is the same as that described in step 1 of Example 1.

[0037] (2) Mixing sol of sodium alginate, ferrous sulfide and zero-valent iron is the same as that described in step 2 of Example 1, except that 0.5 g of sodium alginate is weighed.

[0038] (3) Preparation of sodium alginate-stabilized zero-valent iron-modified ferrous sulfide composite material is the same as described in step 3 of Example 1.

[0039] Example 3

[0040] This embodiment provides a method for preparing a composite material of sodium alginate-stabilized zero-valent iron modified ferrous sulfide (the mass ratio of ferrous sulfide to zero-valent iron is 1:1, and the mass ratio of sodium alginate to ferrous sulfide is 1:1), the method comprising the following steps:

[0041] (1) The mixed solution of ferrous sulfide and zero-valent iron is the same as that described in step 1 of Example 1.

[0042] (2) Mixing sol of sodium alginate, ferrous sulfide and zero-valent iron is the same as that described in step 2 of Example 1, except that 2.5 g of sodium alginate is weighed.

[0043] (3) Preparation of sodium alginate-stabilized zero-valent iron-modified ferrous sulfide composite material is the same as described in step 3 of Example 1.

[0044] Comparative Example

[0045] This comparative example provides a method for preparing a sodium alginate-stabilized modified ferrous sulfide composite material, which is different from Example 1 in that 2.5 g of zero-valent iron is not added.

[0046] The different composite materials prepared by the preparation methods shown in Examples 1-3 and Comparative Examples were used to treat laboratory simulated NO3 - -N wastewater. The different composite materials prepared in Examples 1-3 and the comparative example were placed in a 150mL small anaerobic reactor, the dosage of the composite material was 5g / L, the influent nitrate nitrogen concentration was 63.8mg / L, the hydraulic retention time was set to 5d, and the continuous operation results are shown in Table 1.

[0047] Table 1 Experimental results of embodiments and comparative examples

[0048]

[0049] It can be seen that the nitrate nitrogen removal effects of Examples 1-3 are better than those of the comparative example, indicating that the antioxidant properties and stability of the composite material are significantly improved. In addition, the material prepared in Example 1 with a mass ratio of 3:5 has a good nitrate nitrogen removal effect on nitrates. This is because too low alginate concentration cannot play a spatial hindrance role and thus cause the agglomeration of nano-ferrous sulfide, while too high alginate concentration will increase the acidity of the system. Considering comprehensively, the mass ratio of sodium alginate to ferrous sulfide in Example 1 is selected to be 3:5.

[0050] The sodium alginate-stabilized zero-valent iron-modified ferrous sulfide composite material prepared in the above Example 1 was subjected to an autotrophic denitrification process, simulating a low carbon-nitrogen ratio water body as the influent of the shake flask experiment, the dosage of the composite material was 5 g / L, the hydraulic retention time was 5 days, and 10 mL of domesticated denitrifying anaerobic sludge was added at the same time, and 4 cycles of denitrification operation for a total of 20 days were carried out. The domesticated denitrifying anaerobic sludge was in direct contact with the sulfur autotrophic denitrification filler, and the denitrifying bacteria were enriched in the reactor. The zero-valent iron and ferrous sulfide in the composite material were used as denitrification electron donors, and sodium bicarbonate was used as a carbon source to carry out a denitrification reaction based on sulfur autotrophic denitrification. No additional organic carbon source was added to the reaction influent, and the total nitrogen concentration was 63.8 mg / L. Within four cycles, the nitrate nitrogen removal rate can reach up to 86% (removal effect as shown in Figure 2). Figure 1 ), which can achieve efficient removal of nitrate nitrogen.

[0051] The sodium alginate-stabilized zero-valent iron-modified ferrous sulfide composite material prepared in Example 1 was subjected to scanning electron microscopy analysis before and after the denitrification reaction. Figure 2 As shown in (A), before the reaction, the gel spheres have rich pore structures, significantly increased surface area, and increased effective reaction area. The denitrification electron donor elemental sulfur is embedded in the filler surface, which is conducive to the biofilm enrichment of sulfur autotrophic denitrifying microorganisms. Figure 2 As shown in (B) and (C), a large number of small particles can be observed on the surface of the material and aggregated together, indicating that the composite material is utilized during operation to complete the denitrification reaction. Figure 3 As shown, the composite material was analyzed by XRD. There is a diffraction peak spectrum corresponding to iron in the figure, indicating that Fe 0 It has been successfully encapsulated in SA colloidal particles. The XRD curve after the reaction has a clear stacking peak at around 71°, indicating the formation of an amorphous material, which may be an amorphous chelate formed by iron ions and SA. This further confirms that the prepared composite material can inhibit Fe by forming Fe-SA chelates and reducing the formation of iron oxide. 0 To further analyze the changes in the valence state of the elements in sulfide-based materials, this study conducted XPS tests (see the results). Figure 4). The red fitting lines in A1-B1 and A2-B2 are formed by the superposition of different valence states of iron and sulfur elements, respectively. Different color blocks represent the relative areas of the valence states of the elements. Figure 4 As shown, the Fe and S elements of the composite material are mainly Fe 2+ and S 2- Fe 3+ , S 2- and S n 2- .

Claims

1. A ferrous sulfide composite material for removing nitrate from water, characterized in that: The composite material is a cross-linked product of sodium alginate and calcium chloride as a skeleton, and ferrous sulfide and zero-valent iron are embedded in the skeleton; the preparation method thereof comprises the following steps: (1) Weighing sodium alginate, ferrous sulfide and zero-valent iron powder and adding them into a headspace bottle filled with deionized water, ultrasonically treating them in an ultrasonic cleaner, placing the headspace bottle on a magnetic stirrer for stirring, and obtaining a sol; The mass ratio of sodium alginate to ferrous sulfide is 1-5:5; the mass ratio of ferrous sulfide to zero-valent iron is 1:1; (2) using a disposable syringe to extrude the sol prepared in step (1) into a calcium chloride solution to obtain sodium alginate hydrogel microspheres; during the entire gelation process, the calcium chloride solution is stirred to accelerate mass transfer and prevent the gel microspheres from sticking together; (3) pouring the hydrogel microspheres obtained in step (2) into deionized water and filtering through gauze; then repeatedly rinsing with deionized water until the impurities and excess calcium ions and chloride ions on the surface of the composite gel microspheres are washed away, and then freeze-drying the prepared sodium alginate hydrogel microspheres to obtain a sodium alginate-stabilized zero-valent iron modified ferrous sulfide composite material.

2. A ferrous sulfide composite material for removing nitrate from water as claimed in claim 1, characterized in that: In step (1), the mass ratio of sodium alginate to ferrous sulfide is 3:

5.

3. A ferrous sulfide composite material for removing nitrate from water as claimed in claim 1, characterized in that: In step (1), the deionized water is purified with N2 for 20 minutes.

4. A ferrous sulfide composite material for removing nitrate from water as claimed in claim 1, characterized in that: In step (2), the mass fraction of the calcium chloride solution is 2%.

5. The ferrous sulfide composite material for removing nitrate from water as claimed in claim 1, characterized in that: In step (3), the freeze-drying temperature is -40°C and the freeze-drying time is more than 24 hours.

6. Use of the ferrous sulfide composite material as described in any one of claims 1 to 5 in removing nitrate from surface water and groundwater.

Citation Information

Patent Citations

  • Preparation method and applications of ferrous sulfide / biological carbon composite material

    CN106966456A

  • Preparation method and application of biochar simultaneously immobilizing ferrous sulfide and zero-valent iron

    CN111229160A

  • A sulfurized nano-zero ferric acid activated montmorillonite composite material, its preparation method and application

    CN111718719B

  • Application of montmorillonite-supported vulcanized nano zero-valent iron in removal of pollutants

    CN117383682A

  • Spherical hydrotalcite-like compound-sodium alginate hydrogel adsorbent as well as preparation method and application thereof

    CN117599755A